Effectiveness of Teaching Emotion Regulation Strategies in Improving Cognitive-Emotional Regulation Among Female Students in Addiction-Stricken Areas of Kermanshah City - Afsaneh Shahbazirad; Mona Azizi (Tehran University of Medical Sciences, 2019)
Objective: To evaluate emotion regulation as one of the important aspects of preventing and treatment of substance abuse. Materials and methods: This study had a quasi-experiment research method and a pretest-posttest design with the control group. The statistical population of this study included all the female students who lived in the addiction-stricken areas of Kermanshah city. 60 female students (mean: 16.78 and standard deviation: 0.69) who were eligible to participate in the study were selected by convenient sampling and were placed randomly in two test and control groups. The tools that were used in this study included Granefski et al. (2007) cognitive-emotional regulation scale and demographic information sheet. Eight weekly sessions of emotion regulation strategies based on Gross method (2002) were held for the experimental group. Results: Multivariate covariance analysis results indicated that teaching emotion regulation strategies has been effective in improving adapting strategies and reducing maladaptive strategies of emotion regulation (p < 0.05). Conclusion: Therefore considering the effectiveness of the mentioned intervention, this strategy can be applied beside other methods in order to improve adaptive emotion regulation and reducing maladaptive strategies among female teenagers who live in addiction-stricken areas